Natural ways to prevent and treat oral cancer - Shweta Danaraddi; Anila Koneru; Santosh Hunasgi; Surekha Ramalu; M Vanishree (Wolters Kluwer Medknow Publications, 2014)
Oral cancer is one of the usual causes of mortality all over the world, with a five-year survival rate of only 50%. Oral cancers are treated primarily by surgery with / without adjuvant radiotherapy and / or chemotherapy. However, there is significant post-treatment morbidity and mortality secondary to recurrences. Dietary supplements like fruits and vegetables are rich in phytochemicals and provide a variety of antioxidants like vitamin A, C, E. Spirulina, Selenium, Green tea (EGCG), Neem, Tomatoes (lycopene), Turmeric (curcumin), and some medicinal mushrooms are also used as chemopreventive and chemotherapeutic agents. This overview emphasizes on natural therapies to fight against oral cancer. Thus, there are several natural compounds that can enhance the prevention of oral cancer.